Chemical Composition of Royal Jelly and its Use in Traditional Medicine - Sherali ugli, Yaqubov Xojiakbar; Mahsutali ugli, Mo‘yidinov Muslimbek (American Journal of Biology and Natural Sciences, 2025)
This article provides information about the importance of bee products in traditional medicine and the chemical composition of royal jelly. Methods of obtaining royal jelly and conditions for its storage are described. Information about treating various diseases with preparations made from royal jelly is also presented.